Forms that think - Ruiz Martínez, Natalia (Re-visiones, 2024)
In chapter 3A of Histoire(s) du cinéma, Godard writes “A thought that forms a form that thinks”, implying the complete formulation of certain ideas that go round this work, that is to say, cinema is a powerful creator of forms, and it was originally conceived for thinking.